Social entrepreneurship - Santos, José de Freitas (2014)
The purpose of this chapter is to contribute to a better understanding of the link between social entrepreneurship and institutional environment in Portugal. A quantitative approach is used in the study, with primary data collected through an online survey. A questionnaire was emailed to both Portuguese Non-Governmental Organizations and projects available on the Portuguese Social Stock Exchange. In the analysis of the data, we used descriptive statistics, factorial analysis and t-student tests in an attempt to validate the research hypotheses. The results show that a favorable institutional environment has low importance in the decision to develop social entrepreneurial initiatives. This conclusion supports the idea that many social entrepreneurs can emerge even in developing regions where the institutional environment is weak. Therefore,social entrepreneurship could be an instrument of regional development and contribute to attenuating the social and economic differences among Portuguese regions.